The Performing Art as a Practice of Actual Intoning - Verkina, Tatyana; Bondarenko, Maria; Sagalova, Anna; Timofeyeva, Kira (Journal of History Culture and Art Research, 2020)
The article considers the musical and performing arts as a special creative practice, i.e. as a special way of anchoring, recreating, and developing a person’s musical experience through musical intoning. Musical performing practice functions as an oral discourse and includes, in addition to the text itself (the original one – the note text, and the resulting one – the acoustic text), the processes of its creation and understanding that are unfolding themselves in time. Musical and performing art accumulates its experience of intoning, first of all, in the real sound practice. It is in the process of performance that music is actualized, gaining an existence in time in the living intoning. Intoning is presented as a process of a special kind of communicative relations and is generalized through several concepts and categories of the style level which are associated with performance (the performing practice, performing dramaturgy, and performing style). One of the specific styles that are most illustrative in terms of solving the artistic and technical problems of a complex order is the piano performance (wider – the pianism). The development and enrichment of the existing music experience is only possible in its actualization. Musical art is revealed as the "actual being of a composition" in the process of performing it for listeners, on a specific instrument, in a particular hall.